2007
DOI: 10.1080/08880010701533611
|View full text |Cite
|
Sign up to set email alerts
|

MARKERS OF BONE METABOLISM IN EUGONADAL FEMALE PATIENTS WITH Β-Thalassemia MAJOR

Abstract: Osteoprotegerin (OPG) and receptor activator of NF-kappaB ligand (RANKL) have been recently implicated in the pathogenesis of various types of osteoporosis. The aim of this study was to investigate bone turnover in eugonadal female patients with this disease and characterize the possible role of the OPG/RANKL system in thalassemia-related bone loss. Markers of bone turnover and bone mineral density (BMD) were measured in 16 eugonadal young females with beta-thalassemia major and 18 age- and sex-matched healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…At molecular level, although osteoblast dysfunction is considered to be the main pathogenetic mechanism (19), recent evidence has demonstrated that anemia, through stimulation of erythropoietin and subsequent bone marrow expansion, also increases expression of RANKL and thus promotes activation of osteoclast activity (21,25). In accordance with previous studies (20,26) bone resorption marker b-CTX was found significantly increased at baseline compared with the control group. In addition, P1NP but not osteocalcin was also found increased in these patients, reflecting increased bone turnover.…”
Section: Discussionsupporting
confidence: 79%
“…At molecular level, although osteoblast dysfunction is considered to be the main pathogenetic mechanism (19), recent evidence has demonstrated that anemia, through stimulation of erythropoietin and subsequent bone marrow expansion, also increases expression of RANKL and thus promotes activation of osteoclast activity (21,25). In accordance with previous studies (20,26) bone resorption marker b-CTX was found significantly increased at baseline compared with the control group. In addition, P1NP but not osteocalcin was also found increased in these patients, reflecting increased bone turnover.…”
Section: Discussionsupporting
confidence: 79%
“…6,18 Accordingly, elevated markers of bone resorption have been found in TM subjects. 14,36 Endocrinopathies are common in TM patients, and these may also contribute to osteopenia-OP syndrome, particularly hypogonadotrophic hypogonadism. 37 Anti-resorption therapies, such as bisphosphonates in combination with hormone replacement regimens, lead to improvements in bone integrity in thalassemic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Most have reported increased bone resorption (serum CTx, urinary NTx, deoxypyridinoline) [1,10,34,35,36], with and without decreases in bone formation markers (bone specific alkaline phosphatase, osteocalcin) [1,32-35]. In 2003, Domrongkitchaiporn et al analyzed iliac crest bone biopsies and markers of bone turnover in 18 adult patients with thalassemia.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Many factors contribute to the etiology of low bone mass including: ineffective erythropoiesis which leads to bone marrow hyperplasia [6], growth hormone and sex steroid deficiencies [1,2], hypothyroidism [7], vitamin D deficiency [8], and severe anemia [6,9] with presumed, but poorly characterized reduced physical activity. Even well transfused patients with normal gonadal function who are supplemented with calcium have been shown to have low bone mass by dual x-ray absorptiometry (DXA) [1,10], suggesting other factors are also involved.…”
Section: 0 Introductionmentioning
confidence: 99%